The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1186/s13073-016-0333-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tumor profiling approaches and genomic data strategies for cancer precision medicine

Abstract: BackgroundThe diversity of clinical tumor profiling approaches (small panels to whole exomes with matched or unmatched germline analysis) may engender uncertainty about their benefits and liabilities, particularly in light of reported germline false positives in tumor-only profiling and use of global mutational and/or neoantigen data. The goal of this study was to determine the impact of genomic analysis strategies on error rates and data interpretation across contexts and ancestries.MethodsWe modeled common t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 51 publications
(49 reference statements)
1
135
1
Order By: Relevance
“…WES and WGS will likely be most useful for determining factors that may indicate response to immunotherapy, such as predicted formation of neoantigens [48]. While these techniques also offer a highly accurate measure of mutational burden, it has recently been shown that NGS panels may suffice for this [49, 50]. Tarczy-Hornoch et al [51] have surveyed potential methods for properly integrating WES and WGS information within EHRs.…”
Section: Current Status Of Genomic and Related Informationmentioning
confidence: 99%
“…WES and WGS will likely be most useful for determining factors that may indicate response to immunotherapy, such as predicted formation of neoantigens [48]. While these techniques also offer a highly accurate measure of mutational burden, it has recently been shown that NGS panels may suffice for this [49, 50]. Tarczy-Hornoch et al [51] have surveyed potential methods for properly integrating WES and WGS information within EHRs.…”
Section: Current Status Of Genomic and Related Informationmentioning
confidence: 99%
“…Recent work has shown that mutational load and neoantigen load might be more useful biomarkers of response than specific driver gene mutations [47]. Similarly, the determination of mutational load and neoantigen expression is more predictive when whole exome data are used compared to large or small gene panels [48]. …”
Section: Matching the Test To The Intended Usementioning
confidence: 99%
“…Some groups do not use matched normal material. In order to minimize false-positive calls, these groups either focus on calling previously characterized driver events in known oncogenes (in the case of hotspot panels), or use advanced filtering methods—unmatched normal, PoN, large germline databases (for example, 1000 Genomes, ExAc)—to remove non-somatic variants [48]. Specificity can be further increased by review of candidate mutations by an experienced molecular pathologist and cross-referencing somatic mutation databases such as COSMIC for pathogenicity information [48].…”
Section: Analytical Considerationsmentioning
confidence: 99%
“…Furthermore, although the molecular landscapes of many cancers have been revealed using precision oncology approaches, many of the alterations observed in patients remain undruggable, and viable targets are incompletely characterized. In addition, a considerable amount of diversity exists regarding the types of molecular tests being offered clinically [8]; combined with the knowledge gap regarding the interpretation of genomic test results within the field of clinical oncology, this diversity has fostered confusion among physicians about the meaning and the clinical utility of genomic data at the point of care [9]. Perhaps most critically, prospective trials of molecular profiling across cancers in an unselected manner are not yet mature.…”
mentioning
confidence: 99%